EVALUATION OF ORAL HYGIENE AND DENTAL CARIES STATUS IN PATIENTS WITH BETA THALASSEMIA - Shadlinskaya, R.V. (World of Medicine and Biology, 2020)
The study involved 321 patients with a homozygous form of thalassemia and 382 somatically healthy individuals. For the objective evaluation of teeth hard tissues and oral hygiene, the following clinical tests were performed: Simplified Oral Hygiene Index (OHI-S) (Green J.C., Vermillion, J. R., 1960), index by Yu.A. Fedorov and V.V. Volodkinа (1971), DMFT index. Comparative analysis revealed a significant difference between the indices of the DMFT index and the index of OHİ-S in the groups. There was a tendency to deterioration of the hygienic index with advancing age of patients with thalassemia. The highest values were found in the group over the age of 18 (3.60±0.11). Thus, preventive dental care is a top priority for patients with β-thalassemia.